Data Warehouse Sebagai Sarana Penunjang Penyusunan Borang Akreditasi Standar 4 Pada Program Studi Sistem Informasi Institut Bisnis dan Informatika Kwik Kian Gie - Elis Sondang Dasawaty; Jesaja Waterkamp (Jurnal Informatika dan Bisnis, 2013)
The need for information also requires development and strengthening of cooperation with externalparties to improve the quality and continuity of the Tridarma process in undergraduate program.External parties include government institutions such as Dikti, Kopertis Region III, NationalAccreditation Board (BAN), and local governments; and also the private sector such as company,institute, foundation, university, organization. Accreditation is a tool or instrument to gather informationabout the performance of study program, faculty or college in order to control the quality of alluniversities in Indonesia and serves to capture information related to the quality of the implementationof the study program. This study uses descriptive qualitative research based on case studies thatillustrate the real situation of the investigated object. Data collection methods that used in this studywas observation, interviews, and literature review as a basic deductive hypothesis. Documents that usedin this study are documents of borang accreditation standard 4. Based on the data collection of thedocuments obtained, then continued by analysis of needs (requirements definition). Data warehousemodel was designed and tailored to the needs of the institution can provide strategic information tosupport filling borang accreditation standard 4. It also can be used as a reference for decision makerslevel in study program to support planning and evaluation process in human resources.